PROBLEMS AND SOLUTIONS TO IMPROVE THE EFFICIENCY OF USING ELECTRONIC INFORMATION RESOURCES AT UNIVERSITIES IN UZBEKISTAN (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The relevance of studying the needs of users of global information resources in scientific and educational institutions of Uzbekistan, access to which is provided as part of a National subscription, is due to several factors: despite the expansion of access to electronic databases of leading foreign publishers and aggregators and an increase in the number of universities in the republic, statistics on the use of these resources leaves much to be desired, the passive work of library staff to promote information resources in universities and research centers, the lack of interaction of information resource centers with departments for the training of scientific and pedagogical personnel and academic work, the low level of information culture of young scientists, teachers, researchers and applicants about current sources of scientific information in their organization and in public libraries of the country, the lack of knowledge and skills to work with international databases of scientific and analytical information. In order to receive feedback from users of global information resources and study their needs, a survey was conducted. Based on the analysis and generalization of the survey data, proposals are formulated to enhance the use of scientific and educational resources in universities and research centers: in each information resource center of the university and research center, select a responsible specialist for organizing trainings, master classes on working with electronic resources and their promotion, organize regular webinars on working with certified trainers databases and analytical systems in Uzbek for teachers, doctoral students, applicants and researchers.